2020
DOI: 10.1155/2020/8866369
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Cold Plasma on Quality Retention of Fresh-Cut Produce

Abstract: In recent years, the consumption of the fresh-cut products has been increased due to the consumers’ lifestyle and awareness. However, maintaining the quality and nutritional value of these products during storage is being difficult in comparison to whole fruits and vegetables. In actual, the procedures used in the fresh-cut industry may intensify the deterioration caused by physical damage by minimal processing. Commonly, the quality degradation, discolouration, loss of moisture, loss of firmness, microbial lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 52 publications
(85 reference statements)
0
15
0
Order By: Relevance
“…57 Decomposition of ascorbic acid could be due to the reaction of reactive plasma species, light sensitive oxidation during the treatment. [58][59]…”
Section: Ascorbic Acid Contentmentioning
confidence: 99%
“…57 Decomposition of ascorbic acid could be due to the reaction of reactive plasma species, light sensitive oxidation during the treatment. [58][59]…”
Section: Ascorbic Acid Contentmentioning
confidence: 99%
“…However, in most studies, the focus of interest is only the stability of vitamin C (ascorbic acid) under different processing conditions. Some critical factors that may contribute to the degradation of vitamin C are plasma gas, sample type, and processing time (Bagheri & Abbaszadeh, 2020). Furthermore, ultraviolet light generated by cold plasma may also reduce the content of ascorbic acid as it is sensitive to light (Starek et al, 2019).…”
Section: Effect Of Cold Plasma On Physicochemical Attributes Of Fresh...mentioning
confidence: 99%
“…To maintain the quality of fresh‐cut produce, it is necessary to apply appropriate packaging and store it in cold conditions. (Bagheri & Abbaszadeh, 2020). Many food industries are applying additional preservation methods like ozone (Liu, Chen, et al, 2021), edible coatings (Martiñon et al, 2014), and modified atmosphere packaging (MAP) (Wilson et al, 2019) to restrict the physical damage caused by biochemical reactions, thereby retaining the quality of fresh‐cut produce.…”
Section: Introductionmentioning
confidence: 99%
“…The application of cold plasma is widely used in the whole and minimally processed fruit and vegetable industry as an innovative technology used to handle microbial development [ 55 ], with the aim of replacing conventional sanitation treatments, meanwhile preserving the nutritional and antioxidant aspects of food products. Several scientific studies reported the effectiveness of non-thermal plasma on different horticultural products ( Table 1 ).…”
Section: Postharvest Strategies To Extend the Shelf-life Of Fruit And...mentioning
confidence: 99%